An analysis of passengers' ride needs of urban rail transit services: Application of quality function deployment - Catherine Y. P. Chan; Kwai Sang Chin; Candace K. Chan; Kwok-Leung Tsui (International Journal of Quality Innovation, 2019)
This study aims to suggest using the interpretation type of deployment of quality function deployment (QFD) as a methodology to understand the passengers' needs when they situate in the train cars of urban rail, using the East Rail Line (ERL) in Hong Kong as a case study. The result shows that behaved environment and safe stand are the two most important ride needs demanded by the everyday ordinary passengers of the rail line. In addition to this, the members of the study team reflected that the deployment process has greatly helped them on acquiring a thorough understanding of the passengers' needs, which is very essential for deriving innovative solutions. Besides the rail company could make use of the case study for improving its train ride quality, the suggested methodology is applicable to understand the passengers' ride needs of other kinds of public transport as well as the recipient needs of those public services that are of similar nature.
Keywords: 650; Quality function deployment; Voice of the customer; Passengers' needs; Train ride; Urban rail transit services